Genetic susceptibility to childhood acute lymphoblastic leukemia shows protection in Malay boys: Results from the Malaysia-Singapore all study group - Yeoh, A.E.J.; Lu, Y.; Chan, J.Y.S.; Chan, Y.H.; Ariffin, H.; Kham, S.K.Y.; Quah, T.C. (Elsevier, 2010)
To study genetic epidemiology of childhood acute lymphoblastic leukemia (ALL) in the Chinese and Malays, we investigated 10 polymorphisms encoding carcinogen- or folate-metabolism and transport. Sex-adjusted analysis showed NQO1 609CT significantly protects against ALL, whilst MTHFR 677CT confers marginal protection. Interestingly, we observed that NQO1 609CT and MTHFR 1298 C-allele have greater genetic impact in boys than in girls. The combination of SLC19A1 80GA heterozygosity and 3'-TYMS -6bp/-6 bp homozygous deletion is associated with reduced ALL risk in Malay boys. Our study has suggested the importance of gender and race in modulating ALL susceptibility via the folate metabolic pathway. (C) 2009 Elsevier Ltd. All rights reserved.